Parent perceptions of a group telepractice communication intervention for autism. (January 2022) - Garnett, Robyn; Davidson, Bronwyn; Eadie, Patricia
Background & Aims: Estimates suggest that one in 59 children receive a diagnosis of autism and that early intervention can be effective if applied consistently and intensively. Parent implemented intervention can increase intervention consistency and intensity however, availability of providers, geographical factors, time constraints, and parental stress levels can all act as barriers to service access. Limitations in understanding elements that support family engagement can also impact participation in intervention. Telepractice can increase availability of intervention services and decrease the time and costs associated with face-to-face delivery. Research focused on children with autism has shown that telepractice is acceptable to parents. Despite positive findings for telepractice services with individual clients, limited research has been conducted on telepractice services for parent groups; parent perceptions and preferences regarding intervention; and service delivery methods. This research aimed to investigate parent perceptions of a group intervention programme for autism; the telepractice approach; parent and child outcomes; and parental stress. The purpose of the investigation was to build an understanding of parent's intervention preferences to inform future service offerings, increase choice, and support participation. Methods: Eleven parents of preschool children with autism participated in a telepractice delivered group training programme called Hanen More Than Words (HMTW). The intervention is traditionally delivered face to face and teaches strategies to facilitate social-communication development in young children. Quantitative and qualitative measures were used to evaluate parent perceptions of the telepractice HMTW intervention. Data were collected via the Parenting Stress Index, HMTW programme evaluation forms, and online parent survey. Quantitative data was analysed using descriptive statistics. Pre- and post-intervention comparisons of parenting stress were conducted using paired T-Tests. Open comment field responses were analysed qualitatively using a directed content analysis. Results: Parents reported high levels of satisfaction with telepractice delivered HMTW across intervention and post programme evaluations. Interactive learning opportunities, group participation, video coaching, individualisation of service, and programme facilitation were identified as key supports to learning. Parents perceived increased insight into the interaction, learning, and behaviour of themselves and their children. They reported positive changes in strategy implementation and confidence. Parents also perceived improvements in their children's communication, responsiveness, interaction, and play following intervention. Parental stress measurements from pre- to post intervention, were not significantly different. Conclusions: Telepractice may reduce service barriers and improve access, particularly with the efficiency of a group delivery approach. Utilising technology to deliver group intervention was acceptable to parents and perceived to have positive outcomes for both parent and child. Further investigation into parent perceptions of intervention types and delivery approaches, could facilitate a broader understanding of family needs with respect to service access and engagement. Implications: Expansion of telepractice offerings can increase efficiencies and service choice for families and providers. Limitations in service availability and barriers to service access and engagement, confirm the importance of pursuing ongoing service improvements and evaluating the preferences of service users. Development of standardised tools to measure and compare parent perceptions across intervention types and service delivery approaches would be beneficial.